Penerapan Model Project Based Learning dalam Meningkatkan Kemampuan Berpikir Kritis dan Kolaborasi pada Pembelajaran Biologi Berbasis Enterpreneurship - Aska, Aska; Wicaksana, Ervan Johan; Zurweni, Zurweni (Bhinneka: Jurnal Bintang Pendidikan dan Bahasa, 2026)
The keywords are required for computerization. Research and abstract title search made easy with these keywords. This study aims to determine the application of the entrepreneurship-based Project-Based Learning (PjBL) model to improve students' critical thinking and collaboration skills in Biology lessons at MAN 2 Tanjung Jabung Timur. This study used the Classroom Action Research (CAR) method, implemented in two cycles: Cycle I and Cycle II. Each cycle consisted of planning, implementation, observation, and reflection. Data collection techniques included observation, assessment, evaluation, reflection, and observation sheets for students' critical thinking and collaboration skills. The results showed that the implementation of the entrepreneurship-based PjBL model improved student learning outcomes, critical thinking skills, and collaboration. Assessment scores increased from 62 in Cycle I to 83 in Cycle II, representing a 33.87% increase. Evaluation scores increased from 73 to 93, representing a 27.40% increase, while reflection scores increased from 76 to 91, representing a 19.74% increase. Students' critical thinking skills also improved in the focus, reason, inference, situation, clarity, and overview indicators, which were dominated by categories 3 and 4 in Cycle II. Furthermore, students' collaborative skills improved across indicators of shared understanding, taking appropriate action, and team regulation. Based on the research results, it can be concluded that the implementation of the entrepreneurship-based Project-Based Learning (PjBL) model is effective in improving students' critical thinking and collaboration skills in Biology.